Process Mineralogy and Recovery Process of a Copper Oxide Mine in Niger - Dianqiang HUANG; Yiqi CUI; Youming XIAO; Jing WANG; Yang ZHANG; Xiong TONG (Kuangchan zonghe liyong, 2025)
Taking a copper oxide ore from Niger as a research object, a detailed process mineralogical study on the raw ore was carried out by chemical analysis, X-ray diffraction analysis and optical microscope analysis. The results show that the original ore contains 6.04% copper, 65.07% of which is free copper oxide and 31.95% is bound copper oxide, respectively, which is a high binding rate copper oxide ore. The metallic minerals in the ore are mainly malachite, blue copper ore, silica malachite, pyroxene, pyrite and limonite, and the vein minerals include potassium feldspar, plagioclase, quartz and black mica, which is a complex mineral composition. Most of the copper in the original ore exists in the form of blue copper ore and malachite, and is mainly embedded in quartz, feldspar and other veinlets. The combined flotation-leaching process was proposed in the paper. After flotation, a copper concentrate with a copper grade of 28.23% and a recovery of 56.18% was obtained, and the tailings were directly leached with dilute sulfuric acid, with a leaching rate of 91.15% and a comprehensive recovery of 96.25% copper.